The hy3 Long Hypocotyl Mutant of Arabidopsis Is Deficient in Phytochrome B. - Somers, DE (1991)
The six long hypocotyl (hy) complementation groups of Arabidopsis (hy1, hy2, hy3, hy4, hy5, and hy6) share the common feature of an elongated hypocotyl when grown in white light. The varied responses of these mutants to irradiations of differing wavelengths have suggested that some of the lines may lack elements of the phytochrome signal transduction pathway. We have performed immunoblot and RNA gel blot analyses of the multiple types of phytochrome present in wild-type and mutant Arabidopsis and provide evidence that mutations at the HY3 locus cause a specific deficiency in phytochrome B. Using an Escherichia coli overexpression system, we have developed and identified monoclonal antibodies that selectively recognize phytochromes A, B, and C from Arabidopsis. In wild-type plants, phytochrome A is highly abundant in etiolated tissue, but rapidly decreases about 200-fold upon illumination. Phytochromes B and C are present at much lower levels in etiolated tissue but are unaffected by up to 24 hr of red light illumination, and together predominate in green seedlings. These data establish that phytochromes B and C are "type 2" or photostable phytochromes. Levels of phytochromes A, B, and C similar to those of the wild type are observed in strains containing mutations at the HY4 and HY5 loci. In contrast, all four hy3 mutant alleles tested here exhibit a modest (twofold to threefold) reduction in phyB transcript and a severe (20- to 50-fold) deficiency in phyB-encoded protein, relative to levels in wild-type plants. The levels of phyA- and phyC-encoded mRNA and protein, however, are indistinguishable from the wild type in these mutants. We conclude that the phenotype conferred by hy3 is due to the reduced levels of the light-stable phytochrome B.